Impacts of Federal and State Hazard Mitigation Policies on Local Land Use Policy. (March 2014) - Berke, Philip R.; Lyles, Ward; Smith, Gavin
Despite emergence of federal policy experiments, knowledge about the influence of federal policies on local land use policy is almost nonexistent. We examine the effects of a federal mandate and a federal incentive program on adoption of land use policies in local hazard mitigation plans. Comparative statistics were used to determine adoption rates by federal and state programs, followed by Poisson regressions to explain degree of adoption under the federal policies controlling for state policies and local contexts. We found that federal policies do not make a difference in local land use actions, but state policy exerts a strong influence.